An Analysis of Mediation Process of Sumbawa-Bali Ethnic Conflict On 2013 (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2025)
This reasearch is titled Analysis of the Mediation Process of the Sumbawa-Bali Ethnic Conflict 2013. This conflict is one of the significant events involving social tensions between two ethnic groups, triggred by social jealousy and economic inequality. This study aims to deeply analyze the mediation process, especially in building effective dialogue to create sustainable conflict resolution. This research uses a qualitative approach with a case study method. Data collection techniques were conducted through in-depth interviews and document analysis with research subjects including Mediators from the Sumbawa Regency Regional Government, in this case handed over to the Religious Harmony Forum (FKUB), representatives of the conflicting parties, namely Parisada Hindu Dharma Indonesia (PHDI), and several involved actors, namely the Secretary of the Tana Samawa Traditional Institution (LATS). Data was analyzed using the Miles and Huberman technique, which includes Data Reduction, Data Presentation, and Conclusion Drawing. The results show that the conflict mediation process did not directly involve representatives from both parties, namely the Samawa ethnic group and the Bali ethnic group, so the mediation stages of the PUSAD Paramadina theory were not carried out, neither the problem identification stage nor the problem-solving stage. Mediation focused more on formal resolution, such as law enforcement and physical reconstruction, without addressing the main root causes, namely, socio-economic inequality. This led to a lack of deep dialogue and long-term peace in conflict resolution.